Methods Used to Evaluate the Immediate Effects of Airway Clearance Techniques in Adults with Cystic Fibrosis: A Systematic Review and Meta-Analysis - Naomi Chapman (MDPI AG, 2021)
This review reports on methods used to evaluate airway clearance techniques (ACT) in adults with CF and examined data for evidence of any effect. Sixty-eight studies described ACT in adequate detail and were included in this review. Frequently reported outcomes were sputum expectoration (72%) and spirometric lung function (60%). Compared with cough alone, following any ACT, there was a trend for greater sputum wet weight, however FEV1 was not different. The mean (95% CI) within-group effect for sputum wet weight following any ACT was 12.43 g (9.28 to 15.58) (n = 30 studies) and for FEV1 was 0.03 L (−0.17 to 0.24) (n = 14 studies). Meta-regression demonstrated that, when compared with cough alone, greater sputum wet weight was reported in groups that received additional ACT by between 2.45 and 3.94 g (F3,66 = 2.97, p = 0.04). These data suggest the addition of ACT to cough alone may optimise sputum clearance; however, FEV1 lacked sensitivity to detect this change. Importantly, this review highlights the lack of appropriate measures to assess ACT efficacy.